The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/jocn.12805
|View full text |Cite
|
Sign up to set email alerts
|

The experience of learning to speak up: a narrative inquiry on newly graduated registered nurses

Abstract: Cultivating a safe and open culture of communication and mentoring new graduates to speak up will benefit patient safety now and in the future by helping to retain committed patient advocates who could mentor future generations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 24 publications
2
86
0
1
Order By: Relevance
“…Chandler, [10] Law and Chan [11] and this study found that fresh nursing graduates have high expectations from themselves and others as they are expected to take up their new role and adapt to a new environment in a short period of time. Expectations cause an increased level of anxiety as they worry about being gossiped about or criticised by colleagues which echoes Kelly & Ahern, [9] Morales [22] and Teoh, Pua & Chan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chandler, [10] Law and Chan [11] and this study found that fresh nursing graduates have high expectations from themselves and others as they are expected to take up their new role and adapt to a new environment in a short period of time. Expectations cause an increased level of anxiety as they worry about being gossiped about or criticised by colleagues which echoes Kelly & Ahern, [9] Morales [22] and Teoh, Pua & Chan.…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] They expect to adapt and learn new roles immediately; they feel frustrated when they fail to meet their own or others' expectations. [3,5,10,11] They also fear duty handover and hesitate to speak up when there is a need to communicate with physicians, senior nurses, patients and relatives. [3,8,11,12] In addition, they are discouraged when they find variance between theory and practice in clinical contexts which causes them a lack of confidence and poor clinical performance, [12][13][14][15][16][17][18] given their lack of sufficient knowledge, skills, and experience to bridge the gap.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The recommendations were classified under the following themes: respect and honesty; a health service that is well led; competent health-care professionals; the safety of care; care of an appropriate standard; public involvement through empowerment; and the care of children. Although there was no explicit recommendation on whistleblowing, a number of recommendations foreshadowed some of those of later reports, such as 'a duty of candour' to patients (recommendation 33), a framework of regulation independent of government (recommendations [39][40], doctors' Code of Professional Practice incorporated in the contract of employment (recommendation 45), a regulatory body, and professional code of practice for health-care managers (recommendation 91), a national reporting system (recommendations [109][110][111][112], and incentives to encourage the reporting of sentinel events (recommendations 113-118).…”
Section: Consequences For the Nhsmentioning
confidence: 99%
“…Although there was no explicit recommendation on whistleblowing, a number of recommendations foreshadowed some of those of later reports, such as 'a duty of candour' to patients (recommendation 33), a framework of regulation independent of government (recommendations 39 and 40), doctors' Code of Professional Practice incorporated in the contract of employment (recommendation 45), a regulatory body, and a professional code of practice for health-care managers (recommendation 91), a national reporting system (recommendations [109][110][111][112], and incentives to encourage the reporting of sentinel events (recommendations [113][114][115][116][117][118]. However, more generally, stress was placed on changing the 'culture of the NHS'.…”
Section: Consequences For the Nhsmentioning
confidence: 99%
See 1 more Smart Citation